Contribution of electrocardiography to the diagnosis of cardiomyopathies and athletic heart syndrome - O. S. Chumakova; M. Yu. Isaeva; O. S. Koroleva; D. A. Zateyshchikov (Российский кардиологический журнал, 2020)
The review describes the role of electrocardiography in the diagnosis of the most common nonischemic myocardial diseases associated with an increased risk of sudden cardiac death, especially in youth sports.